Mesenchymal Stem Cells and NF-κB Sensing Interleukin-4 Over-Expressing Mesenchymal Stem Cells Are Equally Effective in Mitigating Particle-Associated Chronic Inflammatory Bone Loss in Mice - Zhang, Ning; Utsunomiya, Takeshi; Lin, Tzuhua; Kohno, Yusuke; Ueno, Masaya; Maruyama, Masahiro; Huang, Ejun; Rhee, Claire; Yao, Zhenyu; Goodman, Stuart B. (Frontiers in Cell and Developmental Biology, 2021)
Wear particles from total joint arthroplasties (TJAs) induce chronic inflammation, macrophage infiltration and lead to bone loss by promoting bone destruction and inhibiting bone formation. Inhibition of particle-associated chronic inflammation and the associated bone loss is critical to the success and survivorship of TJAs. The purpose of this study is to test the hypothesis that polyethylene particle induced chronic inflammatory bone loss could be suppressed by local injection of NF-kB sensing Interleukin-4 (IL-4) over-expressing MSCs using the murine continuous polyethylene particle infusion model. The animal model was generated with continuous infusion of polyethylene particles into the intramedullary space of the femur for 6 weeks. Cells were locally injected into the intramedullary space 3 weeks after the primary surgery. Femurs were collected 6 weeks after the primary surgery. Micro-computational tomography (µCT), histochemical and immunohistochemical analyses were performed. Particle-infusion resulted in a prolonged pro-inflammatory M1 macrophage dominated phenotype and a decrease of the anti-inflammatory M2 macrophage phenotype, an increase in TRAP positive osteoclasts, and lower alkaline phosphatase staining area and bone mineral density, indicating chronic particle-associated inflammatory bone loss. Local injection of MSCs or NF-kB sensing IL-4 over-expressing MSCs reversed the particle-associated chronic inflammatory bone loss and facilitated bone healing. These results demonstrated that local inflammatory bone loss can be effectively modulated via MSC-based treatments, which could be an efficacious therapeutic strategy for periprosthetic osteolysis.